Monotone Points in Orlicz-Bochner Sequence Spaces (Analysis in Theory and Applications, 2012)
In Orlicz-Bochner sequence spaces endowed with Orlicz norm and Luxemburg norm, points of lower monotonicity, upper monotonicity, lower local uniform monotonicity and upper local uniform monotonicity are characterized.
Keywords: Banach lattice; Orlicz-Bochner space; Luxemburg norm; Orlicz norm; upper (lower) monotone point; upper (lower) locally uniformly monotone point.